THE RELATIONSHIP BETWEEN KNOWLEDGE AND PREVENTIVE BEHAVIOR HIV/AIDS AMONG STUDENTS AT DUTA BANGSA UNIVERSITY SURAKARTA - Gusmao, Moises; Utomo, Endrat Kartiko; Firdaus, Insanul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Background: HIV is an acronym for Human Immunodeficiency Virus, a virus that can potentially cause AIDS. The human immune system is vulnerable to infection because this virus specifically attacks white blood cells (CD4), making the body less effective at fighting disease. AIDS, which stands for Acquired Immune Deficiency Syndrome, is a series of symptoms caused by the HIV virus,which weakens the immune system. As a result, HIV/AIDS is a fatal disease for which there is no cure and has become a serious public health problem throughout the world, including in Indonesia. Objective: The purpose of this study was to determine the relationship between knowledge and HIV/AIDS prevention behavior among students at Duta Bangsa University in Surakarta.Method: This study used a cross-sectional design to analyze the correlation. A total of 96 students were selected as samples using proportional random sampling. After ensuring its validity and reliability, a closed questionnaire was used to collect data. The Chi-Square test was used for data analysis.Results: A statistically significant correlation between the level of knowledge and HIV/AIDS prevention behavior was found in this study (p-value ? 0.05). Prevention behavior was better among students who had more information. Conclusion: There is a significant correlation between understanding and HIV/AIDS prevention behavior among university students. More extensive health education and awareness campaigns are needed to improve students' understanding and reduce the risk of HIV/AIDS transmission on campus.